Hysteroscopic morphological pattern reflects histological grade of endometrial cancer. Issue 8 (9th May 2019) - Miyamoto, Taito; Abiko, Kaoru; Murakami, Ryusuke; Furutake, Yoko; Baba, Tsukasa; Horie, Akihito; Hamanishi, Junzo; Mandai, Masaki
Abstract: Aim: To examine the hysteroscopic morphological features in each histological grade of endometrial cancer, and to distinguish high‐ and low‐grade cancer and low‐grade cancer and atypical endometrial hyperplasia (AEH), using hysteroscopy. Methods: In total, 135 patients who underwent hysterectomy after hysteroscopy were analyzed. They were divided into four categories: benign lesion; AEH; low‐grade cancer, including endometrioid carcinoma grades 1 and 2 (G1/2); and high‐grade cancer, including endometrioid carcinoma grade 3 and other high‐grade carcinomas (G3/others). Three blinded gynecologic oncologists independently evaluated hysteroscopic video images for abnormal vessels, surface smoothness, papillary structure and polypoid structure. Prevalence rates of each finding were compared between the four categories. The accuracy of blind biopsy in outpatient settings and hysteroscopic endometrial biopsy in the four categories were also investigated. Results: The number of patients with benign lesions, AEH, G1/2 and G3/others was 8, 7, 84 and 36, respectively. Patients with G3/others exhibited more polypoid (86% vs 61%, P = 0.0095) and less papillary (59% vs 80%, P = 0.023) structures than those exhibited by patients with G1/2. AEH and G1/2 were indistinguishable using hysteroscopy. Hysteroscopic biopsy was more accurate than outpatient biopsy in patients with G3/others (84% vs 52%, respectively, P = 0.010). Both biopsies were not sufficiently accurate to diagnose AEH (outpatient; 0%, hysteroscopic; 57%). Conclusion: Hysteroscopic papillary and polypoid structures can help distinguish between high‐ and low‐grade cancer. Hysteroscopic differentiation between AEH and low‐grade cancer is difficult. These findings are considerable in preoperative assessment to determine adequate surgical strategies.